Spatiotemporal Analysis of Photovoltaic Potential in Ordos City Based on an Improved CRITIC Method - Yifei Guo; Lanwei Zhu; Liduo Dou; Yuxin He; Meiqing Wu (Land)
In view of the contradiction between the still-high energy consumption in Ordos and the increasingly urgent carbon-neutral goal, the adjustment of energy structures has begun, and strategic planning of photovoltaic facility construction critically supports the sustainable growth of local energy systems. Therefore, the author constructed the site selection evaluation system of photovoltaic suitability based on remote sensing, meteorological and topographic data. The improved CRITIC empowerment method is used to comprehensively consider the conflict and variability of the indicators for an objective and quantitative analysis of the spatial and temporal changes in suitable areas for photovoltaic development. Finally, the comprehensive evaluation results of the photovoltaic site selection are obtained. The results show that (a) the improved CRITIC method reduces the weight of ‘night light’ from 0.24 to 0.14, effectively reducing the weight bias caused by the extreme value and (b) since 2010, the regional area of suitable level and above has increased from 23.96% to 48.24%, and its spatial center of gravity shows a trend of moving first to northeast and then to southwest. This study overcomes the limitations of mainstream subjective evaluation methods. Additionally, it addresses the oversight of human factors’ impact on suitability in traditional assessment frameworks. This research provides decision-making support for regional energy allocation planning and spatial planning.